Intergroup Relation-Based Conflict Resolution Patterns to Junior High School Students - Saefulloh, Ahmad; Karliani, Eli; Triyani, Triyani; Gunawan, Vincentius Abdi (Jurnal Pendidikan dan Pengajaran, 2021)
Conflicts between junior high school students cannot be underestimated or left unchecked so that it drags on and causes ongoing conflicts if a settlement pattern and root cause are not found immediately. This study aims to analyze the pattern of intergroup relation-based conflict resolution carried out by junior high school students. This article is the result of research conducted using the development (R&D) method with the stages of needs analysis, development, and testing. The data collection method was carried out by distributing questionnaires to public junior high schools randomly consisting of 799 respondents, namely 329 male and 470 female. Data processing is done by grouping student answers based on research indicators in order to obtain a conflict resolution model used by students. The results showed that the pattern of intergroup relation-based conflict resolution carried out by junior high school students and equivalent in solving problems, students were more dominant in choosing how to communicate, either through cellphones or meeting in person to discuss the root causes of the problems that occurred then reconciled by apologizing to each other, do not do violence, avoid emotions, say rude, high-pitched, to avoid fights. As for students who use violence in an effort to solve problems, it will occur if one of their friends shows opposition and resistance, has a high-pitched tone to speak harshly so that it ignites excessive emotions and causes fights.